Inovasi Kuliner Lokal Dalam Rangka Meningkatkan Kunjungan Wisatawan Di Desa Pardinggaran, Kabupaten Toba - Muhammad Rizal Sitepu (Tourism, Hospitality And Culture Insights Journal, 2023)
Ombus-ombus typical Batak food is food that comes from the Batak language which means blowing. This food is called ombus-ombus because this food is usually eaten or served hot and that means that to enjoy this ombus you need to blow it first. Usually this food will be more delicious when served with sweet tea or hot coffee. It is not clear since when this confectionary began to "become cultured". However, at certain Batak ceremonial events, ombus-ombus is usually the dessert at the event. Ombus-ombus is made from selected rice flour, which is mixed with white sugar and stirred with grated coconut and some uses brown sugar and then wrapped in banana leaves and then steamed like making other rice flour snacks. The rice flour used is selected flour and cannot be arbitrary, while the coconut must be grated by hand (manually) because if you use a machine grater, the starch will be lost, and the banana leaf wrapping used is also not arbitrary, namely the 'ucim' type (top leaves) because it really influences the ombus-ombus taste. Ombus-ombus is unique because one side of the leaf is folded into a square, and these are arranged tightly in bunches, then put in cans that are placed on bicycle carts so that this is what keeps ombus-ombus warm even though they are sold all day long. So it is on this basis that we are interested in raising a research title on local culinary innovations in order to increase tourist visits to Toba Regency.